Digital Watermark Copyright Protection with QR Code - Hazim Alkawaz, Mohammed; Waili, Tuerxun; Iwana Imran , Nur Aqila (International Journal on Perceptive and Cognitive Computing, 2020)
Technology field is growing rapidly that innovation is happening way faster than we can adapt. In this era of rapid developing technology, changes occur constantly and the creation of smartphones has cultivated such improvements as people are more connected now more than ever due to the Internet. In this paper, a digital watermark copyright protection with QR code will be built of which be able to provide more advantages in the time of protecting copyright. Introducing a windows-based or standalone program where QR code will be the new feature of the watermark program. The QR code generator will be the new feature introduce where user can put any preferable link that will direct user who scanned the QR code to the website.